Resposta da saúva atta capiguara gonçalves, 1944 (Hymenoptera: Formicidae) a açúcares e edulcorantes artificiais - Boaretto, Maria Aparecida Castellani (2003)
Using of toxic baits made of dehydrated citric pulp to control grass-cutting ants can lead to unsatisfactory results because of the low attractiveness of the substrate to worker ants. This work aimed to identify attractive substances, with potential for incorporation in a matrix of granulated baits for grass-cutting ants, among several kinds of sugars and substances used in artificial sweeteners. Experiments were carried out in mature nests of Atta capiguara (Hym.: Formicidae) set in pasture. Studied substances were sucrose, fructose, soluble starch, raffinose, maltose, lactose, sorbose, cellobiose, arabinose, xylose, glucose, galactose, rhamnose, arabinose, melezitose, saccharine and cyclamate (at 5.0% w/v). Later, on maltose, xylose, sucrose, fructose and glucose solutions were included at 5.0%, 7.5%, 10.0% and 20.0% w/v, respectively. Cellulose rectangles were used as vehicle and number of rectangles carried into the colonies was evaluated. Carrying rates were very low with maximum means of 9.6% for lactose and 6.0% for arabinose and cyclamate, at the 5.0% concentration. No differences (P > 0.05) were observed relatively to the control (distilled water). No effects were detected for solution, concentration and for the interaction of these factors. Sugars and artificial sweeteners studied were not attractive to Atta capiguara workers, turning their inclusion as attractants in toxic ant baits not viable.